(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
In today’s rapidly evolving software landscape, Agile methodologies emphasize flexibility, iterative delivery, and customer-centric development. However, the increasing complexity of software systems, distributed teams, and accelerated release cycles pose challenges for making timely and accurate decisions. Data-driven decision making (DDDM), empowered by artificial intelligence (AI) and advanced analytics, has emerged as a critical enabler for enhancing decision quality, optimizing workflows, and improving project outcomes in Agile environments. This article explores the integration of AI and analytics into Agile software development processes, highlighting how real-time insights from development metrics, user feedback, and operational data can guide backlog prioritization, sprint planning, risk management, and continuous improvement. Machine learning models, predictive analytics, and natural language processing facilitate forecasting delivery timelines, identifying potential bottlenecks, detecting defects early, and aligning development efforts with business objectives. The study also addresses challenges, including data quality, model interpretability, integration with existing Agile practices, and skill gaps, providing recommendations for effectively embedding AI-driven analytics into Agile workflows. Real-world applications demonstrate that organizations leveraging DDDM in Agile achieve faster release cycles, improved software quality, better stakeholder alignment, and more informed strategic decisions. In conclusion, the convergence of AI, analytics, and Agile methodologies transforms decision making from intuition-based to evidence-driven, enabling software development teams to respond proactively to change, enhance value delivery, and maintain competitive advantage in a dynamic digital landscape.